Electrochemical Synthesis of trans-Olefins from Buta-1,3-dienes and Alkyl Halides - Zhang, Haoxiang; Guo, Lin; Yang, Chao; Xia, Wujiong (Synthesis, 2023)
A facile electrochemical alkylation reaction of buta-1,3-diene derivatives with alkyl halides has been developed, generating highly selective trans-olefins as major products. This method exhibits significant advantages, including simple operation, mild conditions, and convenience of scale-up, and provides a novel route for the synthesis of trans-olefins.
Keywords: electrochemical reduction; trans-olefins; 1,3-dienes; alkyl halides; radicals